2007
DOI: 10.1086/522523
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus (HSV) Suppression with Valacyclovir Reduces Rectal and Blood Plasma HIV‐1 Levels in HIV‐1/HSV‐2–Seropositive Men: A Randomized, Double‐Blind, Placebo‐Controlled Crossover Trial

Abstract: Background. Herpes simplex virus type 2 (HSV-2) infection is common among human immunodeficiency virus (HIV)-infected persons, and HSV reactivation increases plasma and genital HIV-1 levels. We studied HIV-1 levels during HSV suppression in coinfected persons in a placebo-controlled crossover trial.Methods. Twenty antiretroviral therapy (ART)-naive HIV-1/HSV-2-seropositive men who have sex with men in Lima, Peru, with CD4 cell counts Ͼ200 cells/L were randomized to receive either valacyclovir at 500 mg twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
155
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 41 publications
8
155
1
Order By: Relevance
“…Although the present report and other smaller trials conducted among women in Burkina Faso and Thailand, and one conducted among homosexual men in Peru, have shown reductions in plasma and genital or rectal HIV viral loads using aciclovir or valaciclovir [42,43], two recently published randomized controlled trials have shown that daily aciclovir does not reduce the risk of HIV acquisition in HSV-2 seropositive, HIV-seronegative individuals. The necessary reduction in the frequency of genital HIV RNA shedding in order to reduce sexual transmission of HIV is unclear.…”
Section: Discussioncontrasting
confidence: 65%
“…Although the present report and other smaller trials conducted among women in Burkina Faso and Thailand, and one conducted among homosexual men in Peru, have shown reductions in plasma and genital or rectal HIV viral loads using aciclovir or valaciclovir [42,43], two recently published randomized controlled trials have shown that daily aciclovir does not reduce the risk of HIV acquisition in HSV-2 seropositive, HIV-seronegative individuals. The necessary reduction in the frequency of genital HIV RNA shedding in order to reduce sexual transmission of HIV is unclear.…”
Section: Discussioncontrasting
confidence: 65%
“…For instance, more than 3200 mg of acyclovir taken per day was associated with improved survival in a meta-analysis of studies among advanced AIDS patients in the pre-HAART era (80), and 800 mg of acyclovir taken twice daily produced decreases in cervicovaginal HIV shedding in HSV-2-HIV-coinfected women in Thailand (81). Valacyclovir may be preferable to study over acyclovir due to its improved bioavailability (54.5% versus 15% to 30%) and significantly decreased pill burden (82); indeed, among women in Burkina Faso (Africa) and MSM in Peru, 500 mg of valacyclovir taken twice daily was associated with reductions in plasma HIV RNA levels of up to 0.53 log 10 copies/mL (47,48). Furthermore, the finding that HSV-2-specific immune responses persist in genital skin long after resolution of clinical symptoms suggests that prolonged doses of such high-potency drugs may be required to fully suppress the effects of HSV-2 infection (83).…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
“…In particular, ACV/vACV treatments are associated with a reduction of HIV-1 load in plasma, semen, cervico-vaginal secretions, and rectal swabs (3,9,11,20,27,45,46) and in plasma during pregnancy (10). Also, several clinical studies, as well as two meta-analyses of a total of 15 randomized clinical studies, demonstrate that ACV/vACV treatment delays progression to AIDS and prolongs the patient's survival (14,22).…”
mentioning
confidence: 99%